Challenges of sustaining wood industries and raw material supply in Nigerian depressed economy (2012)
Engineering drives social, economic and human development and underpins our knowledge of society and infrastructures. It is a major factor in innovation and in the rise and fall of civilization. The challenge of sustaining wood industries and the supply of wood as raw material in Nigeria at this era of economic depression is considered an engineering challenge. It is believed that engineers are specifically trained to defy challenges in order to attain a set goal. Hence, this paper is devoted to reviewing impact of economic depression on wood supply to Nigerian wood sector and accompanying challenges to engineers. The way out was enumerated to include the development of alternative raw material from array of Non-Timber Forest Products (NTFPs) to complement wood supply, development of capacity for local fabrication of wood working machines and continue research on means of developing local methodologies and engineers are to also re-focused to adapt and domesticate modern technologies. If our nation can properly harness its resources and engineering, we would certainly be able to stay afloat of the present troubled economy.